Modeling and analysis of tooth deviations for manufacturing gears using power skiving - GUO Erkuo; LIU Chang; LIU Shulong; YUAN Yayun (Jixie chuandong)
ObjectivePower skiving is a new method in the manufacturing of cylindrical gears, which has significant advantages such as high efficiency and high precision. In order to address the issue of circular errors that occur on gear tooth surface in skiving, a method was proposed to minimize tooth deviations by optimizing the number of tool teeth.MethodsBy analyzing the causes of tooth deviations based on meshing theory for crossed helical gears and considering kinematic relation in gear skiving, a mathematical model incorporating tool eccentricity error was established. The individual impacts of tool eccentricity error, axial feed rate, tool tooth number on gear tooth deviations were thoroughly discussed. A methodology was suggested for controlling tooth deviations through optimal selection of the number of tool teeth.ResultsNumerical calculation and test results show that this method can significantly reduce the circular errors on gear tooth surface.